Molybdenum Catalyzed Acceptorless Dehydrogenation of Alcohols for the Synthesis of Quinolines - Garcia, Beatriz (2024)
Funding Information: . The authors thank Fundação para a Ciência e a Tecnologia (FCT) for projects 10.54499/PTDC/QUI‐QIN/0359/2021, MOSTMICRO‐ITQB, UIDB/04612/20220 and UIPD/04612/2020. The National NMR Facility is supported by CERMAX through project 022162. We also thank C. Almeida for elemental analysis and mass spectrometry at ITQB laboratories. ESI‐HRMS data were provided by the Mass Spectrometry Unit (UniMS), ITQB/IBET. The authors would like to thank the Crystallography Service of the LAQV, Department of Chemistry, NOVA School of Science and Technology, Portugal, for the structural determination of the complexes and 1 6 Publisher Copyright: © 2024 The Authors. ChemCatChem published by Wiley-VCH GmbH.